Arah Politik Hukum dalam Pembangunan Sistem Hukum Nasional Menurut Undang-Undang RPJPN 2005-2025 - shalihah, aini; Abd Muni (Fakultas Syariah Univeritas Islam Madura, 2023)
Every country has a political law that acts as a basic policy for state administrators to determine the direction and content of the law to be formed. State administrators in carrying out their duties and responsibilities certainly have a legal political system like Indonesia which adheres to a democratic system. This is what then needs to be studied more deeply regarding the direction of Indonesian legal politics and this will not be separated from the historical context of how the direction of national legal policy is. Not only that, this paper will also examine how the implementation of the legal political direction is made in making a policy. The method used in this paper is normative and empirical juridical. The results of the research show that the direction of legal politics in the development of the Indonesian legal system is contained in the 2005-2025 RPJPN Law. Meanwhile, in practice, there are still several legal products issued that are not in line with the 2005-2025 RPJPN Law, such as the revision of the KPK Law (UU No. 9 of 2019), the Minerba Law and also the Job Creation Law. From some of these legal products, it can be said that the direction of legal politics in terms of implementation is still not optimal. Because the policies carried out by the government have not been able to achieve the expected democracy.